Painful Legs and Moving Toes Syndrome: Case Report and Review - Mihael Tsalta-Mladenov; Vladina Dimitrova; Silva Andonova (Neurology International)
Introduction: Painful legs and moving toes (PLMT) syndrome is a rare movement disorder characterized by defuse lower limb neuropathic pain and spontaneous abnormal, involuntary toe movements. Objective: The objective was to present a rare case of PLMT syndrome with a triggering area in an adult patient due to multilevel discogenic pathology, to make a thorough review of this disorder and to provide a practical approach to its management. Case presentation: A 59-years-old male was admitted to the neurology ward with symptoms of defuse pain in the lower-back and the right leg accompanied by involuntary movements for the right toes intensified by tactile stimulation in the right upper thigh. Magnetic resonance imaging (MRI) revealed a multilevel discogenic pathology of the lumbar and cervical spine, with myelopathy at C5-C7 level. A medication with Pregabalin 300 mg/daily significantly improved both the abnormal toe movements and the leg pain. The clinical effect was constant during the 90-day follow-up without any adverse effects. Conclusion: Painful legs and moving toes (PLMT) is a condition that greatly affects the quality of life of patients, but which still remains less known by clinicians. Spontaneous resolution is rare, and oral medications are the first-line treatment. Pregabalin is a safe and effective treatment option for PLMT that should be considered early for the management of this condition. Other medication interventions, such as botulinum toxin injections, spinal blockade, or non-pharmacological treatment options like spinal cord stimulation, and surgical decompressions, are also recommended when the conservative treatment is ineffective in well-selected patients.